(untitled) (BRAC University Journal, 2026)
The non-phonetic nature of English spelling leads to unpredictable pronunciation. Thus, Bangla-speaking learners of English mispronounce English monophthongs–short and long vowels as contrasted with diphthongs–since they lack specific knowledge about the contrastive elements of their L2 and L1 monophthongs. In order to help them, this essay discusses the redundant and distinctive features of English and Bangla monophthongs; presents English monophthongs with their Bangla near-equivalents; pairs up English short vowels with their long counterparts in ways helpful to Bangla-speaking learners of English; and lists the non-syllabic (both phonemic and non-phonemic) realizations of English long vowels. Finally, it discusses some implications for learners.